Recent advances in the neuropsychopharmacology of serotonergic hallucinogens - Halberstadt, Adam L. (Behavioural brain research, 2015)
•Serotonergic hallucinogens are classified as phenylalkylamines and indoleamines.•The two classes of hallucinogens produce similar subjective effects in humans and show cross-tolerance.•Hallucinogen effects are primarily mediated by the serotonin 5-HT2A receptor.•Many effects of hallucinogens are mediated in the prefrontal cortex. Serotonergic hallucinogens, such as (+)-lysergic acid diethylamide, psilocybin, and mescaline, are somewhat enigmatic substances. Although these drugs are derived from multiple chemical families, they all produce remarkably similar effects in animals and humans, and they show cross-tolerance. This article reviews the evidence demonstrating the serotonin 5-HT2A receptor is the primary site of hallucinogen action. The 5-HT2A receptor is responsible for mediating the effects of hallucinogens in human subjects, as well as in animal behavioral paradigms such as drug discrimination, head twitch response, prepulse inhibition of startle, exploratory behavior, and interval timing. Many recent clinical trials have yielded important new findings regarding the psychopharmacology of these substances. Furthermore, the use of modern imaging and electrophysiological techniques is beginning to help unravel how hallucinogens work in the brain. Evidence is also emerging that hallucinogens may possess therapeutic efficacy.